Peranan Inisiatif Pribadi pada Industri Skala Kecil: Cross-Case Analysis pada UKM Kopi di Wilayah Aceh Tengah - Ulfah, Tya; Hardjomidjojo, Hartrisari; Anggraeni, Elisa; Safitriyawi, Roja; Lestari, Suci Ayu (Universitas Teuku Umar, 2025)
Global economic competition has affected financial condition in Indonesia. It has also impacted economy in Aceh province as one of producers of agricultural resources. This situation results in great challenges for Indonesia’s business owners as economic booster towards national financial stability. To cope with this problem, the study to analyze entrepreneurial charactersistics was conducted. This study aims to evaluate what traits play a great role for maintaining certain business to stay sustainable despite emerging challenges. A systematic literature review was done prior to this study to design a theoritical framework, which attributed to cases from entrepreneurs globally. The methodology used was cross-case analysis to verify the theoritical framework from previous study. About three business owners from Aceh were interviewed to identify the traits that lead them to survive their business especially during COVID-19 pandemic. The result showed that personal initiative plays a significant role in sustaining the enterprise despite external factors that are associated with it.